The Effect of Attitude Towards Watching MPL ID Tournaments in Cinema, Subjective Norms, Perceived Behavioral Control, E-WOM, and Involvement on Intention Watching MPL ID Tournaments in Cinema - Sakti, Rachmad Pujo; Premananto, Gancar Candra (Southeast Asian Business Review, 2023)
This research examined the effect of attitudes towards watching MPL ID tournaments in cinemas, subjective norms, perceived behavioral control, involvement, and E-WOM on intentions to watch MPL ID tournaments in cinemas. This research used a quantitative approach using multiple linear regression analysis testing techniques. The research data were obtained from questionnaires distributed online via Google Forms to respondents with predetermined criteria. These criteria include being at least 18 years old, being a gamer, and having never watched an MPL ID tournament in a cinema. The total number of respondents obtained was 136 respondents. This study uses a 5-point Likert scale. The study results show that attitudes toward watching MPL ID tournaments in cinemas, subjective norms, involvement, and E-WOM affect intentions to watch MPL ID tournaments in cinemas. However, perceived behavioral control does not positively affect the intention to watch the MPL ID tournament in cinemas.